2022
DOI: 10.1371/journal.pgph.0000316
|View full text |Cite|
|
Sign up to set email alerts
|

Performance evaluation of the Asante Rapid Recency Assay for verification of HIV diagnosis and detection of recent HIV-1 infections: Implications for epidemic control

Abstract: We previously described development of a rapid test for recent infection (RTRI) that can diagnose HIV infection and detect HIV-1 recent infections in a single device. This technology was transferred to a commercial partner as Asante Rapid Recency Assay (ARRA). We evaluated performance of the ARRA kits in the laboratory using a well-characterized panel of specimens. The plasma specimen panel (N = 1500) included HIV-1 (N = 570), HIV-2 (N = 10), and HIV-negatives (N = 920) representing multiple subtypes and geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 51 publications
2
27
2
Order By: Relevance
“…Recency test targets are those clients ≥15 years of age with HIV-1 infection only. As reported by the US CDC, the Asante recency test kit has a high diagnostic sensitivity (>99%) and specificity (> 98%) ( 10 ).…”
Section: Methodsmentioning
confidence: 90%
“…Recency test targets are those clients ≥15 years of age with HIV-1 infection only. As reported by the US CDC, the Asante recency test kit has a high diagnostic sensitivity (>99%) and specificity (> 98%) ( 10 ).…”
Section: Methodsmentioning
confidence: 90%
“…All HIV testing was accompanied by pretest and post-test counselling and followed the national testing algorithm 18. As noted, only persons who were (1) reactive on the first HIV rapid test in the national algorithm (Determine) and (2) had provided verbal consent (ie, eligible for recency testing) were subsequently tested with Asanté HIV Rapid Recency Assay (Sedia Biosciences, Portland, Oregon, USA) simultaneously with the HIV rapid test UniGold 19 20. Verbal consent was the preferred consent format due to the low-risk nature of the surveillance and to better integrate recency testing into Government of Malawi-approved HIV testing guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…It is a strip-test that includes an additional line with the antigen at a limiting concentration to differentiate recent from long-standing HIV infection. The test uses the same peptide of the LAg-EIA but in a rapid test format and has both visual and reader-based interpretation [ 97 , 98 ]. According to the visual reading, the presence of all three lines (control line (CL), positive verification line (PVL), and long-term line (LTL)) indicate long-term HIV infection; the presence of the two lines CL and PVL indicate recent HIV infection; and the presence of only CL supports the absence of HIV infection.…”
Section: Identification and Diagnosis Of Acute/recent Hiv Infectionmentioning
confidence: 99%
“…The strip reader measures the intensity of the three lines (in intensity units-IU). A recent analysis of specimens representing multiple subtypes and diverse geographic origins showed that the sensitivity and specificity of that rapid recency test for HIV diagnosis were higher than 99% and 98.5%, respectively, an overall agreement with LAg-EIA higher than 91%, and a high-level concordance between visual and strip reader-based results [ 31 , 98 ].…”
Section: Identification and Diagnosis Of Acute/recent Hiv Infectionmentioning
confidence: 99%